Can friendship serve as an impetus for safe driving among young drivers?. (April 2015) - Guggenheim, Noga; Taubman – Ben-Ari, Orit
Highlights: We examined the nature of young drivers' friendships and their reflection in safe versus risky driving. Our interpretative framework was Aristotle's conceptualization of three types of friendship. Young drivers' behavior when driving with friends was related to the perceptions of friendship. It was gender- and age-sensitive. Future interventions might foster positive aspects of friendship relationships to enhance safe driving. Abstract: Reckless driving is a key factor in injury and death among young people, especially men, throughout the world. At this developmental stage (ages 17–24), the youngster's behavior, including driving habits, is strongly influenced by the social discourse. Whereas previous studies have investigated the impact of concepts such as peer pressure and the number of passengers in the car, they have dealt little with the overall social relations that characterize young people, particularly, the nature of their friendships and their reflection in safe versus risky driving. Using qualitative phenomenological methodology, the present study relies on 32 semi-structured in-depth interviews to explore the elements of the relationships among young drivers in the context of driving behavior. Aristotle's conceptualization of three types of friendship was employed as the interpretative framework. The findings reveal that a young driver's behavior when driving with friends is associated with the different perceptions of friendship, and is gender and age sensitive. The elements of a friendship of utility (reciprocal interests, practical and beneficial interactions) were connected with safety at all ages and in both genders, and those of a friendship of virtue (responsibility, equality, concern for others) were associated with safe driving among females of all ages and among some of the older male drivers (21–24 years). In contrast, the components of a friendship of pleasure (spending leisure time together, sharing mutual interests) were related to risky and distracted driving, especially among the younger male drivers (17–19 years). It is suggested that interventions might promote safe driving among young people by fostering the positive aspects of their peer relationships.